(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Learners’ biological program encodes genetic prerequisites, which can serve as priority for the adaptation in educational environment, if the genetic potential is manifested in the functional, phenotypic system. The adaptability in the educational environment based on the learners’ genetic prerequisites can be double influential. From one side the educational environment is formulated from the learners’ adapting genetic prerequisites, with moral-psychological atmosphere and interpersonal relationships among the learners. From the other side the educational environment cannot foster learners’adaptation period. Non adaption in the educational environment leads to distortion of effective learning of learners. Teacher’s primary task is to base the learners’ genetic prerequisites to plan a lesson, creating a favorable learning environment for adaptation. The problem: The combination of biological and historical-cultural programs of students’ development is conditioned by its adaptability to the educational environment. In the educational environment teachers should take into consideration learners’ genetic prerequisites and formulate the boundaries/reaction norms/, content and forms. Modern reasearch on the issue: Modern research on the subject has been carried out within the framework of young scientific branches of pedagogy, pedagogical anthropology, pedagogical axiology, pedagogical diagnostics, pedagogical valeology. Analyzing and combining different approaches and opinions, we can say that two conceptual approaches have been formed: 1. Anthropocentric and 2. Eco-centric, which are comparable to human biological and historical-cultural programs in the environment, with the domination of one of the components of the nature-human-education-culture system. Research purpose: Identify the importance of learners’ genetic prerequisites in adapting to the educational environment.